The British title to sovereignty in the Falkland Islands Dependencies (Polar Record, 1956)
In an attempt to settle the dispute between the United Kingdom, Argentina and Chile over sovereignty in the Falkland Islands Dependencies, the United Kingdom made unilateral Applications to the International Court of Justice at The Hague on 4 May 1955. The Applications set out the British title, and asked the Court to declare that the Argentine and Chilean encroachments in British Antarctic territory were illegal and invalid under international law. Both the Argentine and Chilean Governments refused to accept the jurisdiction of the Court.* The United Kingdom Government subsequently expressed its regret at these refusals, and placed on record the fact that it had now taken every step open to it to bring about a peaceful and amicable determination of this question of sovereignty in accordance with the letter and spirit of the Charter of the United Nations. On 18 March 1956 the International Court announced that since neither Argentina nor Chile was prepared to accept the Court's jurisdiction, both cases had been removed from its list.